THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND PROFESSIONAL ETHICS ON AUDITOR PERFORMANCE IN PUBLIC ACCOUNTING FIRMS IN THE CITY OF MEDAN - Harahap, Hary Naldo; Saraswati, Dwi; Arnita, Vina (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
The study was entitled “The Effect of Emotional Intelligence and Professional Ethics on Auditor’s performance Public Accountant Firm in Medan,” it was intended to analyze the effect of emotional intelligence and professional ethics on auditor’s performance on the municipal public accountant firm and prove whether emotional intelligence and professional ethics could improve auditor’s performance.The Study came from our primary data collections of questionnaires, literature, and interviews. The questionnaire in this study was handed out to the auditor’s by purposive sampling method. Data analysis used multiple regression analysis, t test , f test and determinations. Studies show that partial emotional intelligence significantly affects the performance of the auditor’s. It is explained that the t test performed with significant value suggests below 0,05 is 0,000 ˂ 0,05. Then, Partially the professional ethics affect have significant positive effect on the auditor”s performance. This is explained by the results of the t test conducted with results obtained significant value suggest below 0,05 which is 0,034 ˂ 0,005 whereas research results show that together emotional intelligence and professional ethics affect auditor performance. It is explained from the f test done with result obtained a probability value of 0,000 ˂ 0,005. The conclusion was that emotional intelligence and professional ethics had an affect on auditor’s performance on the municipal public accountant firm. The higher emotional intelligence and the higher the level of ethical understanding of an auditor’s profession the better performance. That both of these factors will enhance the performance of an auditor in performing his or her task.